ANALYSIS OF HR TURNOVER AT RSIA RESTU BUNDA, BANDAR LAMPUNG - Syahadah Siregar; Susana Dwi Astuti (Syntax Corporation Indonesia, 2023)
The importance of HR in an organization because it has an important role in helping the organization in achieving its goals. RSIA Restu Bunda, Bandar Lampung which aims to accelerate the achievement of saving the death of pregnant women and their babies to the delivery process requires human resources in it. However, the problem that often occurs is the change of human resources, including in this hospital. This study aims to analyze the turnover of human resources at RSIA Restu Bunda in Bandar Lampung. This research uses a descriptive method with a qualitative approach. Collection techniques with documentation and interview techniques, while data analysis is inductive / qualitative and qualitative research results emphasize meaning rather than generalization by triangulation (combined). The results showed that there are five factors driving HR turnover are dissatisfaction with public facilities, social institutions and welfare in terms of income and ease of access to obtain basic daily needs and relationships with superiors. Thus, the importance of HR management strategies so that there is no change in invention. Some of the roles of HR management in managing HR turnover are the role of the recruitment system, training, compensation and benefits, career development and promotion, rewards and performance appraisals.